2007
DOI: 10.1102/1470-7330.2007.9084
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing benign from malignant liver tumours

Abstract: Liver masses are very common and most are benign. It is therefore important to avoid unnecessary interventions for benign lesions, while at the same time ensuring accurate diagnosis of hepatic malignancies. Many cancer patients, like the general population, have incidental benign liver lesions. In planning treatment for cancer patients, it is critical to avoid inappropriate treatment decisions based on misdiagnosis of a benign lesion as a metastasis or primary liver malignancy. This article describes the salie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 125 publications
(121 reference statements)
0
31
0
2
Order By: Relevance
“…It can be challenging to distinguish between benign and malignant liver disease and to identify and differentiate lesions in the setting of a steatotic ("fatty") or cirrhotic liver 24,25 . Heiken et al 26 reported that 10%-20% of solid benign tumours may display atypical features that could be confused with hepatocellular carcinoma, cholangiocarcinoma, or hypervascular metastases. In addition, hepatocellular adenoma can often have a varied appearance, and certain subtypes such as infiltrative hepatocellular carcinoma can frequently be missed completely by inexperienced radiologists 27,28 .…”
Section: (E)mentioning
confidence: 99%
“…It can be challenging to distinguish between benign and malignant liver disease and to identify and differentiate lesions in the setting of a steatotic ("fatty") or cirrhotic liver 24,25 . Heiken et al 26 reported that 10%-20% of solid benign tumours may display atypical features that could be confused with hepatocellular carcinoma, cholangiocarcinoma, or hypervascular metastases. In addition, hepatocellular adenoma can often have a varied appearance, and certain subtypes such as infiltrative hepatocellular carcinoma can frequently be missed completely by inexperienced radiologists 27,28 .…”
Section: (E)mentioning
confidence: 99%
“…This technique has the advantage of being fast and sensitive when gas is present inside the bowels, and it can give a good representation of all abdominal organs (14). Modern CT equipment combined with a contrast medium provides a reliable imaging method with high spatial resolution in several phases of vessel enhancement enabling imaging of the liver in 1-2 arterial phases, the portal venous phase and later phases if needed to distinguish benign from malignant liver lesions (20,38). The kidneys are easy to examine, identify and define with a CT examination.…”
Section: Ultrasound and Other Modalities For Imaging The Kidneys And mentioning
confidence: 99%
“…Contrast-enhanced ultrasonography (CEUS) has improved both the detection and characterization of focal liver lesions and has been shown to be an important imaging method, and plays a major role in distinguishing benign from malignant liver lesions (15)(16)(17)(18)(19)(20). CEUS can be performed for a variety of indications on practically all parts of the human body (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…LCA specimens are soft and light brown to yellow. 10,17 Spontaneous hemorrhage is possible because of the high-pressure blood supply and bloodfilled sinusoids combined with poor soft tissue support. 3 A study of MRI features and pathology of 20 LA patients found three types of LA cell types: steatotic, peliotic, and mixed.…”
mentioning
confidence: 99%
“…In a study of 15 patients with LA, three had a vascular malformation involving the portal vein that was congenitally absent or thrombosed or had portosytemic venous shunts. 14,17 Along with two theories as to the cause of LA, there are also two types. Multifocal LA tends to be more common in asymptomatic patients.…”
mentioning
confidence: 99%